2020
DOI: 10.1016/j.pacs.2019.100149
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of frequency-domain and delay-and-sum optoacoustic image reconstruction including the effect of coherence factor weighting

Abstract: Image reconstruction in optoacoustic imaging is often based on a delay-and-sum (DAS) or a frequency domain (FD) algorithm. In this study, we performed a comprehensive comparison of these two algorithms together with coherence factor (CF) weighting using phantom and in-vivo mouse data obtained with optoacoustic microscopy. For this purpose we developed an FD based definition of the CF. Our results reveal the equivalence of DAS and FD, with and without CF weighting, in terms of spatial resolution and contrast-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…This is consistent with the observation that the use of the coherence factor weighting does not improve the lateral resolution of an image as stated in Ref. [28]. However, with the help of the coherence factor, the x-artefacts, as well as the background noise could be reduced, which is illustrated by the difference between the two B scans shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the observation that the use of the coherence factor weighting does not improve the lateral resolution of an image as stated in Ref. [28]. However, with the help of the coherence factor, the x-artefacts, as well as the background noise could be reduced, which is illustrated by the difference between the two B scans shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…5(c). We would like to emphasize that the FWHM calculated after the reconstruction method does not provide a direct information about the possible resolution based on the sensor geometry, as it was also pointed out in [28]. Since the microsphere measurements have shown that the FWHM with and without the use of coherence factor weighting hardly changes, we will in the following use the FWHM after the complete reconstruction to interpret the performance of the array.…”
Section: Resultsmentioning
confidence: 96%
“…Reconstruction speeds have been previously accelerated using standard frequency domain reconstruction with experimental optoacoustic data, with a 53 s-reconstruction time for a data size of 200 x 200 x 100 voxels in Fourier domain, compared to nearly 3 hours in time-domain based reconstruction for the same data set 27 , representing a 200-fold faster reconstruction. Recently, Fourier reconstruction times of 0.25 s were reported for B scans with 600 x 751 pixels 44 and of 0.7 s for multi-layer volumetric reconstruction of a 40 x 40 x 2000 voxel-data set 45 . Here we achieve reconstruction times of 6 s for over 40 times larger data sizes than previously demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…21,[39][40][41][42] Acoustic-resolution OA mesoscopy (AR-OAM -Figure 1D, middle) and OA tomography (OAT -Figure 1F, right) are the methods of choice for imaging deeper tissues. AR-OAM is commonly based on raster scanning of a single broadband focused ultrasound sensor, 24,[43][44][45][46][47] whereas OAT is realized with a parallel detection using ultrasound arrays, typically resulting in high imaging speed but inferior spatial resolution due to narrower bandwidth. [48][49][50][51][52][53][54] High-resolution (bandwidth) measurements in the acoustic-resolution regime however come to the detriment of stronger attenuation of ultrasound at high frequencies, which limits the achievable depth.…”
Section: Lis Tening To the S K In With O P Toacous Ti C Smentioning
confidence: 99%